2021
DOI: 10.3390/ijms221910884
|View full text |Cite
|
Sign up to set email alerts
|

Cheonggukjang-Specific Component 1,3-Diphenyl-2-Propanone as a Novel PPARα/γ Dual Agonist: An In Vitro and In Silico Study

Abstract: Background: Cheonggukjang is a traditional fermented soybean paste that is mostly consumed in Korea. However, the biological activities of Cheonggukjang specific compounds have not been studied. Thus, we aimed to discover a novel dual agonist for PPARα/γ from dietary sources such as Cheonggukjang specific volatile compounds and explore the potential role of PPARα/γ dual agonists using in vitro and in silico tools. Methods: A total of 35 compounds were selected from non-fermented and fermented soybean products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…These models revealed that for the PPARγ receptor, the amino acid residue Cys 285 could play a crucial role in the association of pesticides with this receptor, as observed for diflubenzuron [20] or for the organotin compounds TPT and TBT [21]. This interaction was also reported for molecules of a different type such as 1,3-diphenyl-2-propone, volatile organic compounds extracted from a fermented cheonggukjang (Korean food), and the Cys 285 residues of PPARβ/δ and PPARγ [111]. This interaction was confirmed by X-rays to be essential for the interaction between organotin and the PPARY [21].…”
Section: Discussionmentioning
confidence: 69%
“…These models revealed that for the PPARγ receptor, the amino acid residue Cys 285 could play a crucial role in the association of pesticides with this receptor, as observed for diflubenzuron [20] or for the organotin compounds TPT and TBT [21]. This interaction was also reported for molecules of a different type such as 1,3-diphenyl-2-propone, volatile organic compounds extracted from a fermented cheonggukjang (Korean food), and the Cys 285 residues of PPARβ/δ and PPARγ [111]. This interaction was confirmed by X-rays to be essential for the interaction between organotin and the PPARY [21].…”
Section: Discussionmentioning
confidence: 69%